Estimation of Dietary Acrylamide Exposure of Ethiopian Population Through Coffee Consumption - Dhaba Mengesha; Negussie Retta; Henok Ashagrie Deribew; Markos Makiso Urugo; Paulos Getachew (Journal of Food Protection)
This study estimated the acrylamide exposure of the Ethiopian population through traditional brewing of Coffee arabica. Acrylamide concentrations in traditionally processed Ethiopian C. arabica varieties from Jimma, Sidama, Yirgacheffe, Nekemte, and Hararge were measured. A qualitative survey in Addis Ababa was used to develop a traditional coffee brewing flowchart, which was then applied in a laboratory setting. Acrylamide concentrations in roasted coffee powders were found to be 944.01, 861.67, 739.63, 726.35, and 326.60 μg/kg for Hararge, Nekemte, Jimma, Yirgacheffe, and Sidama, respectively. First brew concentrations were 119.97, 112.10, 108.68, 94.07, and 6.67 μg/L, and second brew concentrations were 21.41, 16.45, 16.77, 3.92, and 6.31 μg/L for the respective varieties of Nekemte, Yirgachefe, Jimma, Hararge, and Sidama. Estimated daily intake (EDI) of acrylamide, based on coffee consumption data, were well below harmful levels (<200 μg/kg bw/day), with Target Hazard Quotient (THQ) values indicating minimal noncarcinogenic risk (<1). The study also found low concern for nonneoplastic effects (intake < 0.2 μg/kg bw/day) from Sidama and Nekemte coffees, although a relatively higher concern was observed for Nekemte in specific areas. The findings suggest that reducing acrylamide content in coffee through preventive actions and mitigation strategies is advisable to minimize potential health risks.